Constitutive expression of Yes-associated protein (Yap) in adult skeletal muscle fibres induces muscle atrophy and myopathy. - Robert N Judson; Stuart R Gray; Claire Walker; Andrew M Carroll; Cecile Itzstein; Arimantas Lionikas; Peter S Zammit; Cosimo De Bari; Henning Wackerhage (PLoS ONE)
The aim of this study was to investigate the function of the Hippo pathway member Yes-associated protein (Yap, gene name Yap1) in skeletal muscle fibres in vivo. Specifically we bred an inducible, skeletal muscle fibre-specific knock-in mouse model (MCK-tTA-hYAP1 S127A) to test whether the over expression of constitutively active Yap (hYAP1 S127A) is sufficient to drive muscle hypertrophy or stimulate changes in fibre type composition. Unexpectedly, after 5-7 weeks of constitutive hYAP1 S127A over expression, mice suddenly and rapidly lost 20-25% body weight and suffered from gait impairments and kyphosis. Skeletal muscles atrophied by 34-40% and the muscle fibre cross sectional area decreased by ≈40% when compared to control mice. Histological analysis revealed evidence of skeletal muscle degeneration and regeneration, necrotic fibres and a NADH-TR staining resembling centronuclear myopathy. In agreement with the histology, mRNA expression of markers of regenerative myogenesis (embryonic myosin heavy chain, Myf5, myogenin, Pax7) and muscle protein degradation (atrogin-1, MuRF1) were significantly elevated in muscles from transgenic mice versus control. No significant changes in fibre type composition were detected using ATPase staining. The phenotype was largely reversible, as a cessation of hYAP1 S127A expression rescued body and muscle weight, restored muscle morphology and prevented further pathological progression. To conclude, high Yap activity in muscle fibres does not induce fibre hypertrophy nor fibre type changes but instead results in a reversible atrophy and deterioration.